The Role of Internal Audit in Influencing the Accounting Information System on the Quality of Village Government Financial Reports in Medan Selayang District - Sucipto, Tia Novira (Journal of Management, Economic, and Accounting, 2025)
The purpose of this study is to examine and to analyze the influence of accountancy system utilization and the auditing internal role to the village government’s finance report quality of Medan Selayang District. This kind of this research is quantitative research. The population in this research is the villages’device which located in 6 (six) villages in Medan Selayang District, which the technique of sample taking use saturated sample, so the amount of sample in this research is 48 persons. The data which used in this research are primary data and secondary data which used the questionnaire as the data collection method. The data processing in this uses the SPSS software program. The result in this research shows that the auditing internal role (X1) and the accountancy system utilization (X2) take the partially effect of the finance report (Y) and the auditing internal role (X1) and the accountancy system utilization (X2) take the simultaneously effect to the finance report quality.